1981
DOI: 10.1203/00006450-198107000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Development of Blood Coagulation—A Fetal Lamb Model

Abstract: SummaryTo study the normal development of blood coagulation factor activities in a growing fetus while avoiding the effects of labor and delivery, a chronic fetal lamb model was developed in which serial blood samples from 10 fetuses were studied during the third trimester of pregnancy and 24 hr after birth. Under operating room conditions with sterile technique, a polyethylene catheter to which heparin had been bound to both internal and external surfaces was inserted into the femoral artery of the fetus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…These levels decreased steadily to attain normal adult levels in term fetuses and were unaffected by labor and delivery. Age of the fetus, determined by the induced ovulation technique (1,7,8), correlated inversely with CFI activity in the fetus. This correlation accounted for 93.3% of the change in CFI activity, strongly suggesting that higher CFI activity is a function of fetal immaturity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These levels decreased steadily to attain normal adult levels in term fetuses and were unaffected by labor and delivery. Age of the fetus, determined by the induced ovulation technique (1,7,8), correlated inversely with CFI activity in the fetus. This correlation accounted for 93.3% of the change in CFI activity, strongly suggesting that higher CFI activity is a function of fetal immaturity.…”
Section: Discussionmentioning
confidence: 99%
“…A heparinized catheter was plasma to induce neutro~hil chemotaxis (r = -0-%, P < 0.01), placed in the femoral artery of the fetuses at various gestational suggesting that CFI plays a major role in the regulation of ages under general anesthesia of the ewe (8). A group of eight leukocytes chemotaxis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gestational ages of the fctiiscs were known on the basis of induced ovulation technique (8). Before surgery the cwcs wcrc fastcd for 4 8 h. Anesthesia of the ewe and surgery on the fetus were perfornlcd as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
“…We chose the pregnant sheep because Kisker et al (8), Massicotte et al (9), and Moalic et al (10) previously showed that maturation of coagulation factors in the fetal lamb is similar to that of humans. In addition, one of the authors has observed increased catheter-related thromboses and occlusions in adult (maternal) and fetal sheep with chronic glucose and insulin infusions (W. W. Hay Jr, unpublished observations).…”
mentioning
confidence: 99%